Bringing Research Libraries into Europeana: Establishing a Library-Domain Aggregator - Chambers, Sally; Schallier, Wouter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Europeana’s future strategy requires a domain-level aggregator of library content, positioned alongside other domain aggregators for museums, archives and audio-visual collections. To enable this, LIBER (Association of European Research Libraries), CENL (Conference of European National Librarians) and CERL (Consortium of European Research Libraries) have joined forces to submit the ‘Europeana Libraries’ project proposal to the European Commission in the context of the CIP-ICT PSP-2010-4 ‘Digital Libraries’ programme in early Summer 2010. This paper outlines the vision of the ‘Europeana Libraries’ project, which will enable The European Library to become the library-domain aggregator for Europeana.